1. -6(x + 3) + x = -6x + 30
2. Distribute -6 to the terms inside the parentheses: -6x - 18 + x = -6x + 30
3. Combine like terms on the left side of the equation: -6x + x - 18 = -6x + 30
4. Move all terms with x to one side of the equation: -6x + x + 6x - 18 = 30
5. Simplify: -5x - 18 = 30
6. Add 18 to both sides of the equation: -5x = 48
7. Divide both sides of the equation by -5: x = -27/8
Order the the steps to solve the equation for x. Make sure to put the steps in order. Not all steps will be used just 4.
-6(x + 3) +x = -6x + 30
x = 12
-6x -18 + 4x = -6 x + 30
-6x +3 + 4x = -6x + 30
4x - 18 = 30
-8x + 3 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8
1 answer